(untitled) (Acta Scientiarum. Biological Sciences, 2013)
The aim of this study was to describe the population structure and reproduction of Macrobrachium jelskii from a stream in the central region of São Paulo State. A total of 1,215 specimens was collected monthly during one year (February 2008 to January 2009), being 535 males, 578 females and 102 juveniles. The overall sex-ratio was not significantly different from the expected 1:1, but has significantly differed in some months. A total of 136 ovigerous females were collected and the reproductive period was continuous with peak of occurrence on the hottest months. An increase in juveniles following the highest frequency of ovigerous females was observed and characterized the recruitment period. The fecundity was low and varied from 1 to 56 eggs per female. The biological profile observed here matched, in general aspects, with the pattern developed by tropical and subtropical inland populations, with some particularities related with environmental characteristics.